2014
DOI: 10.1097/brs.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Durotomy During Spinal Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 37 publications
3
29
0
3
Order By: Relevance
“…Scar tissue that adheres to the dura and complicates the surgical differentiation between the two may explain this association. Odds ratios of 2.21 and 4.78, respectively, have been reported by others for the occurrence of DT in patients undergoing revision surgery [8,28]. Our odds ratio was 1.78.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Scar tissue that adheres to the dura and complicates the surgical differentiation between the two may explain this association. Odds ratios of 2.21 and 4.78, respectively, have been reported by others for the occurrence of DT in patients undergoing revision surgery [8,28]. Our odds ratio was 1.78.…”
Section: Discussionsupporting
confidence: 71%
“…Deyo et al also found laminectomy to be associated with a higher incidence of DT [10]. Several studies have demonstrated that previous surgery at the same level is an important risk factor for incidental DT [8,28]. Scar tissue that adheres to the dura and complicates the surgical differentiation between the two may explain this association.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we describe overall rates of 11.3% and 4.5% deviations from a regular peri-operative course caused by surgical and medical factors, respectively, which can be explained by the tertiary care setting with a high proportion of morbid patients, in addition to a high proportion of revision surgeries (approximately one third of cases) and complex procedures. However, these rates lie below or within the rates reported in the literature, to the best of the authors' knowledge [5,[10][11][12][13][14][15][16]. In fact, as reported by Nasser et al [16] in a systematic review including 105 articles, an overall complication incidence of 16.4% per patient was identified, which lies above the herein reported complication rate.…”
Section: Discussionsupporting
confidence: 52%
“…This fact may be attributed mainly to differences in patient cohorts as well as the types of surgical procedures and indications. The majority of these previously published studies reported the overall incidence of dural lacerations across a variety of spinal surgeries [10,12,19,20], such as combined fusion and decompression procedures [7,9,11,21]. For lumbar disc surgery, the previously published incidences of dural tears seem to be relatively low, with reports ranging between 2 and 6 % [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This variation may be attributed to the fact that some studies include all types of lumbar spine surgeries, while other studies focus on decompression procedures exclusively. Risk factors for the occurrence of an incidental durotomy include epidural adhesions associated with previous surgeries, synovial cysts, severe spinal stenosis, increased comorbidities, smoking, and increased patient age [8][9][10][11][12]. Previously published studies investigated whether an incidental durotomy is associated with an inferior outcome after lumbar decompression surgery.…”
Section: Introductionmentioning
confidence: 99%